Cardioprotective Role of Melatonin in Acute Myocardial Infarction - Fu, Zhenhong; Jiao, Yang; Wang, Jihang; Zhang, Ying; Shen, Mingzhi; Reiter, Russel J.; Xi, Qing; Chen, Yundai (Frontiers in Physiology, 2020)
Melatonin is a pleiotropic, indole secreted and synthesized by the human pineal gland. Melatonin has biological effects including anti-apoptosis, protecting mitochondria, anti-oxidation, anti-inflammation, and stimulating target cells to secrete cytokines. Its protective effect on cardiomyocytes in acute myocardial infarction (AMI) has caused widespread interest in the actions of this molecule. The effects of melatonin against oxidative stress, promoting autophagic repair of cells, regulating immune and inflammatory responses, enhancing mitochondrial function, and relieving endoplasmic reticulum stress, play crucial roles in protecting cardiomyocytes from infarction. Mitochondrial apoptosis and dysfunction are common occurrence in cardiomyocyte injury after myocardial infarction. This review focuses on the targets of melatonin in protecting cardiomyocytes in acute myocardial infarction, the main molecular signaling pathways that melatonin influences in its endogenous protective role in myocardial infarction, and the developmental prospect of melatonin in myocardial infarction treatment.